Navigating a Petroleumscape: Shaping transnational oil modernity at the crossroads of global flows and local territories - Sarkhosh, Rezvan (A+BE | Architecture and the Built Environment, 2024)
The thesis explores Ahwaz's transformation throughout the 20th century, emphasizing the profound impact of the oil industry on the city's architectural and urban development. From its emergence in obscurity to its prominence before the Iran-Iraq war, Ahwaz's journey mirrors the far-reaching influence of oil on urban modernity. The narrative weaves a complex tapestry of global dynamics and local distinctiveness, detailing how oil shaped not only the city's landscape but also its identity. The research underscores the intricate interplay between global forces and local characteristics, showcasing Ahwaz as a resilient blend of history, culture, and urban development. It highlights the city's defiance of simplistic categorizations, celebrating its diverse industries and the convergence of global influences. The study concludes by positioning Ahwaz as a living testament to the enduring legacy of the past, an ever-evolving urban canvas that reflects the complex interplay of architecture, culture, and power, perpetuated by the transformative force of petroleum.